Penerjemahan Video Dakwah Syekh Nabil Al-Awadi: Analisis Kesalahan Fonetik Artikulatoris-Auditoris - Mauidlotun Nisa'; Fisqiyah Raudhatul Jannah (An-Nahdah Al-'Arabiyah)
This research aims to reveal the phonetic errors heard and pronounced by several students, and to identify the distribution of phonetic errors in Sheikh Nabil Al-Awadhi's sermon videos. This research is a qualitative-descriptive and library research with a communicative translation approach focused on auditory phonetic analysis. The primary data for this research are the sermon videos on Sheikh Nabil Al-Awadhi's YouTube channel titled "Fadlul al-Dzikr wa al-Baqiyat al-Shalihat" and "Fadlu qira’at al-Quran wa fadlu al-Taqwa." The research identified ten phonetic articulation errors, consisting of 8 consonants and 2 vowels. The consonant articulation errors include sounds ه [h], ل [l], غ [gh], ع [‘a], ض [dl], ظ [ẓ], ق [q], and ط [th], and the vowel errors are أ_ [a:] and -ِ [i]. In listening to and pronouncing Arabic sounds, errors in letter sounds were distributed at the beginning, middle, and end of words. Translating the videos presents the challenge of potential listening errors by the translator, thus necessitating phonetic proficiency.